Supervision of Ethical Compliance and Government Integrity in Improving Accountability and Transparency of Educational Governance - Muhammad Aras Prabowo; Lina Noviana Fadjerini; Taufik Hidayadi; Mohammad Zuhdi; Fitriah Ulfah; Muhammad Ashlyzan Razik; Mariska Nur Hanifah (Mandalika Institute, 2025)
This research aims to analyze supervisory strategies regarding the importance of government ethics in maintaining integrity, accountability and transparency in education administration. The research method used is literature study by collecting from various literature such as books, previous journals, and credible data sources. The research results show that good government ethics increase public trust in the government and help create a clean, effective and efficient government. Governance ethics is an important foundation for good governance and needs to be further strengthened with important contributions to understanding the role of supervision in improving the effectiveness of educational governance.